Efeito da nitretação a plasma e deposição de recobrimento de nitreto de cromo na transição de regimes de desgaste por deslizamento de aços ultrabaixo carbono estabilizados ao titânio - Alexandre de Azevedo Caixeta (2017)
In this work the tribological properties of IF steels were studied in three systems: the substrate - IF steel niobium stabilized; IF steel surface modified by plasma nitriding process in triode configuration (temperature of 500ºC for 6 hours); and a sequential duplex process (plasma nitrided IF steel in triode configuration at the temperature of 500°C for 6 hours, followed by coating of chromium nitride film by deposition process at a temperature in the range of 380 to 420°C and deposition time of 6 hours and 30 minutes). The studied systems were characterized by X-ray diffraction, scanning electron microscopy, energy dispersive X-ray spectroscopy, micro-indentation and 2 and 3D profilometry. The systems were submitted to the dry sliding wear test in sphere on disc configuration. Three normal loads (5, 15 and 30N) and sliding distance of 1600 and 5800m were used. Partial tests with 50 and 200m were performed. The radius of the track used for the wear test was 7mm, and 380rpm, which corresponded to a tangential velocity of 0.229m/s. It was found that the process of plasma surface modification altered the surface morphology of IF steel by introducing a first layer of compounds (εFe2–3N e γ′-Fe4N) followed by a zone of nitrides precipitates in the form of large needles (γ′-Fe4N e CCC α-Fe) and by a zone of precipitates of α″-Fe16N2 in the form of small needles in the ferritic matrix. The process of chromium nitride film deposition, in addition to creating a layer of 7.75μm thickness, altered the nitrogen diffusion, so that the thickness of the layer of compounds was presented with irregular thickness in addition to being observed a refining the large and small needles nitrites precipitated. The Instrumented microhardness tests performed in the cross-section of the materials in the three systems studied indicated that the plasma nitriding process increased up to twice the hardness of the UBC steel to a depth of up to 650μm, whereas the chromium nitride coating increased surface hardness by up to 3.4 times and created a hardness plateau above 3.0GPa to a depth of approximately 800μm. The sliding wear results have shown that UBC plasma-treated steel had a better wear performance with normal load of 30N, reducing the track depth by 53.2% in the 1600m wear test and in 11, 0% in the 5800m test, this difference being associated with the end of the layer of compounds on the wear track surface around 1000m of sliding. On the other hand, the IF nitrided steel + chrome nitride coating showed a reduction of 92.5% and 93.4% wear track depth in sliding distances of 1600 and 5800m respectively. The results indicated a much superior performance of the duplex system compared to only nitrided and unmodified IF.